New Labour Codes in India: A Beginning: Transforming Labour Laws for a Sustainable and Equitable India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The empowerment of workers is necessary for an empowered, prosperous and AatmanirbharIndia. Even after 73 years of Independence, approximately 90 percent of workers work in the unorganisedsectors that do not have access to all the social securities. The total number of workers, comprising oforganised and unorganised sectors, is more than 50 crores. It is for the first time that any Government hascared for the workers in both organised and unorganised sectors and their families. Workers mayapproach the National Industrial Tribunal for settlement of an industrial dispute related to dismissal,retrenchment or termination within 45 days after the after the application for the conciliation of thedispute was made. The Ministry of Labour and Employment introduced four Bills in 2019 to amalgamate29 central laws related to labour laws thereby simplifying and modernising the labour regulations in alabour intensive country, like India. These bills regulate I Wages, (ii) Industrial Relations, (iii) SocialSecurity, and (iv) Occupational Safety, Health and Working Conditions